Efektifitas Media Edukasi Berbasis Audiovisual terhadap Pengetahuan dan Sikap Keluarga Lansia Hipertensi dalam Mencegah Covid-19 - Ni Luh Putu Dian Yunita Sari; Ni Made Dwi Ayu Martini; Ketut Darmaja; Ni Luh Susanti Satryani; I Gusti Agung Kumala Dewi (School of Nursing, Faculty of Medicine, Lambung Mangkurat University., 2022)
Background: One of the vulnerable population in the COVID-19 pandemic is the elderly with hypertension. The family as a support system for the elderly in dealing with illness must have good knowledge and attitudes. Purpose: This study aims to determine the effectiveness of audiovisual-based educational media